Effect of live Salmonella Ty21a in Dextran Sulfate Sodium-induced Colitis - Gunnar Nysœter; Kari Erichsen; Anne Marita Milde; Eva Colás; Einar Kristoffersen; Arnold Berstad (AboutScience Srl, 2007)
Background Intestinal microbiota seems to play an essential role in the development of inflammatory bowel diseases (IBD). We hypothesised that an oral vaccine based on live Salmonella typhi would be well tolerated and could even attenuate dextran sulfate sodium (DSS) induced colitis in rats, an animal model of IBD. Methods Nine male Wistar rats was used for an initial tolerance study, in which we used 3 dose-levels of Salmonella Ty21a, 0.5 × 10 9 , 1 × 10 9 , and 2 × 10 9 CFU, each dose being tested in 3 rats. Four treatment groups consisting of 8 male Wistar rats per group: 1) control group given standard food and water, 2) control group given four daily administrations of Salmonella Ty21a 1 × 10 9 CFU, 3) water with 5% DSS the last 7 days, 4) four daily administrations of Salmonella Ty21a before water with 5% DSS the last 7 days. The Salmonella Ty21a was administered by gastric gavage on day 1, 3, 5 and 16, while DSS was given with the drinking water from day 15 to 22. The animals were sacrificed and colonic tissue removed for analysis 22 days after gavage of the first vaccine dose. Results The animals in the tolerance study got no signs of disease. In the treatment study, all animals receiving DSS had histologic indications of colitis, particularly in the distal part of the colon. Administration of Salmonella Ty21a had no significant effect on crypt and inflammation scores (p > 0.05). Conclusion Gastric administration of live vaccine strain Salmonella Ty21a was well tolerated, but did not provide any significant protection against development of DSS induced colitis in rats.